DAMPAK PSIKOLOGIS PEMBELAJARAN DARING PADA MASA PANDEMI DI MIN 1 SUMENEP - Siti Aisyah (LP3M IAI Al-Qolam Malang, 2021)
The author examines the psychological impact of online learning during the pandemic. Psychology is the study of attitudes. The application of online learning in education, especially among students, has an impact on students' psychology. As a long-term result, students have a lack of social interaction with the surrounding environment, it reduced learning effectiveness, and students could easily feel bored. Online learning is a learning system that is carried out without meeting face to face. Online systems use media and technology that can connect one person to another remotely. The online learning system has been implemented since the pandemic. One of the schools that implements online learning is MIN 1 Sumenep. MIN 1 Sumenep School applies online learning using media such as Whatsapp, Zoom Meeting, and or other applications. In this study, the author uses a qualitative research method in which the instrument is the researcher herself. Therefore, the researcher, as an instrument, must be prepared her objectiveness how far the researchers are ready to carry out research before goes to the field. Data collection techniques were carried out by means of observation, interviews, and documentation. The data analysis uses descriptive analysis method or in other words describes a picture of the object under study through the data or samples that have been collected. The data analysis process begins by examining all available data from various sources. Key words: Psychology of learning, online learning, education, pandemic, impact.